MiR-17–92 cluster is connected with disease progression and oxaliplatin/capecitabine chemotherapy efficacy in advanced gastric cancer patients: A preliminary study. Issue 35 (August 2018) - Fan, Baohua; Shen, Cunfang; Wu, Milu; Zhao, Junhui; Guo, Qijing; Luo, Yushuang
Abstract : Abstract: This study aimed to determine the role of plasma miR-17–92 cluster level in predicting chemoresistance in patients with gastric cancer (GC) undergoing oxaliplatin/capecitabine (XELOX) chemotherapy. Patients recently diagnosed with advanced GC were chosen as participants based on the inclusion criteria. The plasma levels of miR-17-5p, miR-18a, miR-19a/b, miR-20a, and miR-92-1 (miR-17–92 cluster) were determined through quantitative RT-PCR of blood samples from GC patients and healthy volunteers. All the patients received XELOX chemotherapy, and the effectiveness of the chemotherapy was evaluated. The miR-17–92 plasma level was increased in advanced GC patients and decreased after XELOX chemotherapy. Moreover, the miR-17–92 cluster level was associated with chemotherapy response but not with chemotherapy-related toxicity. The miR-17–92 cluster plasma level was decreased in chemosensitive patients, but not in chemoresistant patients, after chemotherapy. The sensitivity and specificity of the combined detection of the miR-17–92 cluster in patients with advanced GC were 100% each. The results suggest that the miR-17–92 plasma level is associated with the progression of advanced GC and effectiveness of XELOX chemotherapy.